2011
DOI: 10.1620/tjem.224.229
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of Adipose Stromal Cells Promotes Neovascularization of Random Skin Flaps

Abstract: The delivery of bone marrow-derived mononulear cells (BM-MNCs) has been proved to be effective at promoting neovascularization of ischemic skin flaps. However, the limited source of BM-MNCs restricts their clinical application. Stromal vascular fraction (SVF) contains a group of heterogeneous cells in the adipose tissue, including adipose tissue-derived stem cells, and it has abundant reserve in human body. In this study, we evaluated the therapeutic potential of SVF to promote neovascularization of random ski… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 18 publications
(27 reference statements)
1
29
0
Order By: Relevance
“…Mechanical stretch during tissue expansion creates a unique microenvironment (Zollner et al, 2013, Zhou et al, 2013) for skin regeneration. With the assist of MNCs, stretched skins are endorsed accelerated angiogenesis (Sheng et al, 2011, Zhou et al, 2013, Sasaki et al, 2008) and growth factor secretion (Yang et al, 2011, Stappenbeck and Miyoshi, 2009). Histological results of the present trial showed that there was a durable increase in the number of proliferating cells in the expanded skin after MNC transplantation (p < 0.01).…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical stretch during tissue expansion creates a unique microenvironment (Zollner et al, 2013, Zhou et al, 2013) for skin regeneration. With the assist of MNCs, stretched skins are endorsed accelerated angiogenesis (Sheng et al, 2011, Zhou et al, 2013, Sasaki et al, 2008) and growth factor secretion (Yang et al, 2011, Stappenbeck and Miyoshi, 2009). Histological results of the present trial showed that there was a durable increase in the number of proliferating cells in the expanded skin after MNC transplantation (p < 0.01).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, Sheng et al (2011) demonstrated that BM-MSC transplantation improves neovascularization by increasing capillary angiogenesis and blood flow perfusion (6). They showed that BM-MSCs, a heterogeneous population of cells, are more beneficial than homogenous compositions in therapeutic vascularization (6).…”
Section: Discussionmentioning
confidence: 99%
“…They showed that BM-MSCs, a heterogeneous population of cells, are more beneficial than homogenous compositions in therapeutic vascularization (6). The effects of BM-MSCs and adipose mesenchymal stem cells (AD-MSCs) on skin flap survival have often been studied in dorsal random skin flaps in rats (5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the recent studies, both BM-MNCs and SVF, have been found to promote the survival of ischemic flaps. [47] With great progress in stem cell therapy, more optimal choices will appear for the treatment of ischemia flaps. But still what is known from these cells is not enough, lots of work have to be done to explore the mechanism of cell therapy, and to improve the survival of transplanted cells as well as their therapeutic effects.…”
Section: Stem Cells and Vascularizationmentioning
confidence: 99%